Peranan Penting Pesantren Dalam Pengembangan Aswaja Dan Sejarah Dan Perkembangan Pesantren Di Nusantara - Bawon Bawon; Mat Rokim; M. Hasan Hidayat (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Islamic boarding schools (pesantren) are the oldest Islamic educational institutions in Indonesia and play a strategic role in the development and transmission of the Ahl al-Sunnah wa al-Jamā‘ah (Aswaja) doctrine. This paper aims to examine the crucial role of pesantren in strengthening Aswaja through a literature review approach drawing on classical texts, works of pesantren scholars, as well as reputable contemporary national and international studies. The discussion focuses on the theological and historical foundations of Aswaja, the pesantren structure encompassing the roles of the kyai, santri, and the kitab kuning curriculum, as well as the dynamics of pesantren in responding to modernization and globalization. The findings indicate that pesantren function not only as religious educational institutions but also as agents of social identity formation, promoters of religious moderation, and guardians of the inclusive tradition of Islam Nusantara. The integration of Aswaja values into the pesantren curriculum has been shown to contribute to the strengthening of tolerant attitudes, a balance between tradition and change, and the ideological resilience of Indonesian Muslims. This paper emphasizes that pesantren occupy a central position in safeguarding the continuity of Aswaja amid contemporary ideological challenges and social transformation, while also serving as an important reference for the development of Islamic education policies in Indonesia.